Dermal Papilla Cell Proliferation of Phytochemicals Isolated from Chestnut Shells (Castanea crenata) - SeonJu Park; Nahyun Choi; Le Nu Huyen Trang; Mira Oh; Youngse Oh; Jong-Hyuk Sung; Seung Hyun Kim (Plants, 2023)
Castanea crenata (Fagaceae) is a species of chestnut tree that is endemic to the Republic of Korea and Japan. While its kernels are consumed, chestnut by-products such as shells and burs, which account for 10–15% of the total weight, are discarded as waste. Phytochemical and biological studies have been carried out to eliminate this waste and develop high-value products from its by-products. In this study, five new compounds (1–2, 6–8) along with seven known compounds were isolated from the shell of C. crenata. This is the first study to report diterpenes from the shell of C. crenata. Comprehensive spectroscopic data including 1D, 2D NMR, and CD spectroscopy were used to determine the compound structures. All isolated compounds were examined for their ability to stimulate dermal papilla cell proliferation using a CCK-8 assay. In particular, 6β,7β,16α,17-Tetrahydroxy-ent-kauranoic acid, isopentyl-α-L-arabinofuranosyl-(1→6)-β-D-glucopyranoside, and ellagic acid exhibited the most potent proliferation activity of all.